(untitled) (Research, Society and Development, 2022)
To investigate whether breastfeeding during the Golden Hour is related to the quality of breastfeeding, using a combination with the LATCH instrument, in a sample of infants from a maternal-infant ward. This is a cross-sectional study, with an exploratory and descriptive approach, developed at the Maternity Hospital of the University Hospital in Cascavel, Paraná, Brazil. This study was approved and approved in 2022 by the Research Ethics Committee, respecting resolution 466/12. The results were analyzed using Excel 365 – Microsoft®, with normal distribution values ​​according to the Shapiro-Wilk test. 109 full-term newborns were analyzed, considering the practice of breastfeeding in the first hour of life and application of the LATCH instrument. The results presented showed that there was a statistically significant difference in the quality of breastfeeding between the averages of newborns who were breastfed during the Golden Hour, in relation to those who were not breastfed. Newborns who did not breastfeed during the Golden Hour had a lower score on the LATCH instrument.